2021
DOI: 10.1177/1475921721989577
|View full text |Cite
|
Sign up to set email alerts
|

Multi-feature integration and machine learning for guided wave structural health monitoring: Application to switch rail foot

Abstract: Switch rails are weak but essential components of high-speed railway systems that have urgent nondestructive testing requirements owing to aging and the associated potential for fatigue damage accumulation. This study presents a multi-feature integration and automatic classification algorithm for switch rail damage using guided wave monitoring signals. A combination of piezoelectric transducers and magnetostrictive patch transducers is adopted to improve the monitoring performance and meet actual monitoring re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Real-world monitoring experiments were conducted to evaluate the proposed method using our previous SHM system (TKMRGW-20, Zheda Jingyi Tech, Ltd Hangzhou, China) [8] (figure 12(a)). To apply the proposed CS method and not increase the cost of hardware when adapting to the existing SHM system, the guided wave data were first collected using the system.…”
Section: Compression Reconstruction and Defect Monitoring Experiments...mentioning
confidence: 99%
See 2 more Smart Citations
“…Real-world monitoring experiments were conducted to evaluate the proposed method using our previous SHM system (TKMRGW-20, Zheda Jingyi Tech, Ltd Hangzhou, China) [8] (figure 12(a)). To apply the proposed CS method and not increase the cost of hardware when adapting to the existing SHM system, the guided wave data were first collected using the system.…”
Section: Compression Reconstruction and Defect Monitoring Experiments...mentioning
confidence: 99%
“…In addition, guided waves can detect large areas in a short time (at the speed of several kilometers per second), which meets the requirements of extremely fast scanning of the HSR. This study is based on our previous works, which proved the effectiveness of guided waves in the switch rail SHM, and the guided wave SHM system has been established [7,8]. It has been operating since 2020 at the national railway-testing center in Beijing, China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the problem of SHM, Buckley et al 39 evaluated different feature selection methods based on the criterion for obtaining the maximum classification performance from some supervised classification algorithms. Liu et al 40 proposed a feature selection method based on binary particle swarm optimization with a new fitness function to choose the useful features and disregard irrelevant and redundant features to improve the classification performance. Wang and Song 41 utilized a feature selection approach called joint mutual information maximization in the problem of bolt-looseness detection.…”
Section: Introductionmentioning
confidence: 99%
“…As guided waves can propagate over relatively long distances, cover large areas and are sensitive to defects, they enable the long-range evaluation of rails from a single test point and have demonstrated great potential in nondestructive evaluation [2][3][4]. Many studies using guide waves focused mainly on the stock rail [5][6][7][8][9][10][11][12], and only a few studies [13][14][15][16][17] have focused on the switch rail. This study builds on our previous works that demonstrated the effectiveness of guided waves in structural health monitoring (SHM) of switch rails [14,15].…”
Section: Introductionmentioning
confidence: 99%